Physical activity and sedentary behavior in college youth from Colombian cities: practices, motivations, and resources (Colombia Medica, 2024)
Purpose: To describe physical activity (PA) practice in college youth from some Colombian universities, and to identify its relation to their motivations (to do it, to not do it, and to change it), and the available resources. Method: A total of 1811 students between 15 and 24 years of age from six Colombian universities participated. The Physical Activity scale from the College Youth Lifestyle Questionnaire was used. Results: It was found that 22.2% of the students have PA practices. The main motivations to practice PA were «to benefit health» (45.8%) and «to look better» (32%), while the reason to not practicing it was «laziness» (61.5%). PA was higher in those who were satisfied with the changes they have made and are planning to maintain them (66%), and in those that have some resources, such as sports accessories, time, abilities, psychical skills, good health status, psychical activities and sports' offer and knowledge on how to perform well. Conclusions: The results show that to prevent and to modify sedentary lifestyles in young individuals, it is necessary to incorporate aspects such as motivations to change and obtaining of resources.